Dedicated Breast Computed Tomography With a Photon-Counting Detector: Initial Results of Clinical In Vivo Imaging. Issue 7 (July 2019) - Berger, Nicole; Marcon, Magda; Saltybaeva, Natalia; Kalender, Willi A.; Alkadhi, Hatem; Frauenfelder, Thomas; Boss, Andreas
Abstract : Objectives: The purpose of this work is to present the data obtained from the first clinical in vivo application of a new dedicated spiral breast computed tomography (B-CT) equipped with a photon-counting detector. Materials and Methods: The institutional review board approved this retrospective study. Twelve women referred for breast cancer screening were included and underwent bilateral spiral B-CT acquired in prone position. Additional sonography was performed in case of dense breast tissue or any B-CT findings. In 3 women, previous mammography was available for comparison. Soft tissue (ST) and high-resolution (HR) images were reconstructed. Two independent radiologists performed separately the readout for subjective image quality and for imaging findings detection. Objective image quality evaluation was performed in consensus and included spatial resolution, contrast resolution, signal-to-noise ratio (SNR), and contrast-to-noise ratio. All women were asked to report about positioning comfort and overall comfort during data acquisition. Results: The major pectoral muscle was included in 15 breast CT scans (62.5%); glandular component was partially missing in 2 (8.3%) of the 24 scanned breasts. A thin "ring artifact" was present in all scans but had no influence on image interpretations; no other artifacts were present. Subjective image quality assessment showed excellent agreement between the 2 readers (κ = 1). Three masses were depicted in B-CT and were confirmed as simple cysts in sonography. Additional 5 simple cysts and 2 solid benign lesions were identified only in sonography. A total of 12 calcifications were depicted with a median size of 1.1 mm (interquartile range, 0.7–1.7 mm) on HR and 1.4 mm (interquartile range, 1.1–1.8 mm) on ST images. Median SNRgl, SNRfat, and contrast-to-noise ratio were significantly higher in ST than in HR reconstructions (each, P < 0.001). A mild discomfort due to positioning of the rib cage on the table was reported by 2 women (16.7%); otherwise, no discomfort was reported. Conclusions: The new dedicated B-CT equipped with a photon-counting detector provides high-quality images with potential for screening of breast cancer along with minor patient discomfort.